Effect of HMM glutenin subunits on wheat quality attributes - Horvat, Tomica (Array, 2009)
Summary: Glutenin is a group of polymeric gluten proteins. Glutenin molecules consist of glutenin subunits linked together with disulphide bonds and having higher (HMM-GS) and lower (LMM-GS) molecular mass. The main objective of this study is the evaluation of the influence of HMM-GS on flour processing properties.